Best Multiplier Approximation of Unbounded Periodic Functions in L_(p,∅_n ) (B),B=[0,2π] Using Discrete Linear Positive Operators (Baghdad Science Journal, 2020)
The purpose of this paper is to find the best multiplier approximation of unbounded functions in –space by using some discrete linear positive operators. Also we will estimate the degree of the best multiplier approximation in term of modulus of continuity and the averaged modulus.